Analisis Beban Kerja Pada Unit Rekam Medis di Rumah Sakit Roemani Muhammadiyah Kota Semarang Tahun 2025 Menggunakan Metode NASA-TLX - Chatarina Lintang Febrilian; Lutfiyah Rizqulloh; Bajeng Nurul Widyaningru (LPPM POLBITRADA, 2025)
The Medical Records Unit plays a crucial role in ensuring the completeness and accuracy of patient information in hospitals. A high workload in this unit can impact Performance and service quality. One of the factors that triggers workload is the transition process from a manual system to Electronic Medical Records (EMR), as occurred at Roemani Muhammadiyah Hospital in Semarang City. This study aims to analyze the workload level of Medical Records Unit staff using the NASA-TLX method, which assesses six dimensions: Mental Demand, Physical Demand, Temporal Demand, Performance, Effort, and Frustration Level. This study design was cross-sectional with a total sampling of six respondents from the Filling, Coding, and Assembling Units. Data were collected using the NASA-TLX questionnaire and analyzed based on the rating score and weighting of each dimension. The results of the study show the average value per dimension, namely: Mental Demand (MD) 480, Physical Demand (PD) 464, Temporal Demand (TD) 420, Performance (P) 440, Effort 420, and Frustration (F) 280. The total overall score is 2,504, with a final NASA-TLX score of 78.25, which is classified as a high workload category. The dominant dimension contributing to the workload is Performance (P). These results are expected to be a reference for hospitals in evaluating work systems and supporting the welfare of staff during the digitalization transition period.